SINGING THE SONGS OF SORROW: A STUDY OF GENDER AND SEXUALITY THROUGH RIMA DAS’ BULBUL CAN SING - Devi, Medha; Ved Prakash (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The paper examines Rima Das’ film Bulbul Can Sing (2018) from the perspective of gender and sexuality. Made in Assamese, it is a coming-of-age story of three friends who have to find their identity, sexuality, and voice through the odds of society. The women characters in the film actively indulge in dialogue and question the traditional patriarchal norms. Indian cinema has mostly constructed a binary with active male and passive female; in this film, the binary is dismantled. The film also subverts the male gaze, making the female not an object of desire but someone who has control over their desires and fantasies. It is a fact that women have to struggle to find their way within the oppressive social framework, and men too have to succumb to the dominant idea of being. Apart from exploring the trope of ‘Women’s Cinema’ and cinema by women filmmakers in India, the paper studies the cinematic shots regarding Bulbul Can Sing to decode various natural tropes and images used as part of the narrative, keeping Auteur theory in mind. The paper also looks into the dominion of female desire and agency concerning Rima Das’s cinema. The paper examines how patriarchy works regressively towards creating and circulating the idea of masculine and feminine. The last part of the paper deals with the issues of patriarchy and toxic masculinity and the impact of the same on the larger mobility of individuals within the social fabric.